2010
DOI: 10.1111/j.1365-2966.2010.16851.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical models of collisions between core-collapse supernovae and circumstellar shells

Abstract: Recent observations of luminous Type IIn supernovae (SNe) provide compelling evidence that massive circumstellar shells surround their progenitors. In this paper we investigate how the properties of such shells influence the SN light curve by conducting numerical simulations of the interaction between an expanding SN and a circumstellar shell ejected a few years prior to core collapse. Our parameter study explores how the emergent luminosity depends on a range of circumstellar shell masses, velocities, geometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 68 publications
6
96
0
Order By: Relevance
“…For example, if the shock collides with a dense shell ejected during a luminous blue variable (LBV) outburst prior to the SN, an extremely bright event in the UV can result that could be detected above z ∼15 (e.g., Smith & McCray 2007;van Marle et al 2010;Moriya et al 2010Moriya et al , 2013Tanaka et al 2012). We are now studying the observational signatures of these superluminous Pop III Type IIn SNe (Whalen et al 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…For example, if the shock collides with a dense shell ejected during a luminous blue variable (LBV) outburst prior to the SN, an extremely bright event in the UV can result that could be detected above z ∼15 (e.g., Smith & McCray 2007;van Marle et al 2010;Moriya et al 2010Moriya et al , 2013Tanaka et al 2012). We are now studying the observational signatures of these superluminous Pop III Type IIn SNe (Whalen et al 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…Other simulations have explored the evolution of the subsequent supernova shock waves within the bubbles [44,45,46,47,43,48]. Although the highly supersonic winds around massive stars (wind velocity on order 1000-2000 km s −1 ), and the low density and high pressure pervading the bubble would point to an extremely high temperature within the bulk of the bubble (of order 10 7 to 10 8 K), X-ray observations have shown that if hot gas is detected at all, its temperature and emission measure are both low, on the order of a few times 10 6 K [49,50,51,52].…”
Section: Bubbles and Superbubblesmentioning
confidence: 99%
“…The bolometric LC is obtained with the hydrodynamics code ZEUS-MP that is combined with a cooling function, which is applicable to the optically thin system. The method is similar to that adopted by van Marle et al (2010). The homologous SN ejecta is assumed to have two density components with n = 9 and δ = 0.…”
Section: Light Curve Propertiesmentioning
confidence: 99%